A menu of standards for green infrastructure in England: effective and equitable or a race to the bottom? - Grace, Mike; Smith, Alison; Mell, Ian; Houghton, Jane; Neal, Peter (Frontiers in Environmental Science, 2025)
Multi-functional urban green infrastructure (GI) can deliver nature-based solutions that help address climate change, while providing wider benefits for human health and biodiversity. However, this will only be achieved effectively, sustainably and equitably if GI is carefully planned, implemented and maintained to a high standard, in partnership with stakeholders. This paper draws on original research into the design of a menu of GI standards for England, commissioned by Natural England—a United Kingdom Government agency. It describes the evolution of the standards within the context of United Kingdom government policy initiatives for nature and climate. We show how existing standards and guidelines were curated into a comprehensive framework consisting of a Core Menu and five Headline Standards. This moved beyond simplistic metrics such as total green space, to deliver GI that meets five key ‘descriptive principles’: accessible, connected, locally distinctive, multi-functional and varied, and thus delivers 5 ‘benefits principles’: places that are nature rich and beautiful, active and healthy, thriving and prosperous, resilient and climate positive, and with improved water management. It also builds in process guidance, bringing together stakeholders to co-ordinate GI development strategically across different sectors. Drawing on stakeholder feedback, we evaluate the strengths and weaknesses of the standards and discuss how they provide clarity and consistency while balancing tensions between top-down targets and the need for flexibility to meet local needs. A crucial factor is the delivery of the standards within a framework of supporting tools, advice and guidance, to help planners with limited resources deliver more effective and robust green infrastructure with multiple benefits.